Perancangan Low Voltage Main Distribution Panel (Lvmdp) Untuk Optimalisasi Distribusi Listrik Mall Karawaci Tangerang di PT Tiga Hutama Teknik - Dzaki, Ilham; Rahmadewi, Reni (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to design a Low Voltage Main Distribution Panel (LVMDP) specifically designed for mall needs, with a focus on optimizing energy distribution, load management, and system reliability. Mall Karawaci Tangerang is a place that is very dependent and requires a continuous supply of electricity as its main energy to operate, but because it is very wide and consists of 3 floors, the need for electricity supply is also very large. The LVMDP panel is an electrical panel that utilizes MCCB as the main system in its security to distribute 3-phase (380V) and 1-phase (220V) electricity. This study used three methods which were applied including literature, observation, and interviews. The results of this study are to produce an electrical panel design that can distribute electricity in the Karawaci mall effectively, safely and optimally.